2005
DOI: 10.1002/glia.20246
|View full text |Cite
|
Sign up to set email alerts
|

Role for CXCR2 and CXCL1 on glia in multiple sclerosis

Abstract: As part of a need to understand myelin repair mechanisms, molecular pathways underlying oligodendrocyte behavior and central nervous system (CNS) remyelination are currently key topics in multiple sclerosis (MS). In the present study, we report expression of a chemoattractant receptor of the immune system, the chemokine receptor, CXCR2, on normal and proliferating oligodendrocytes in active MS lesions. Proliferating oligodendrocytes were occasionally associated with reactive astrocytes positive for CXCL1 (GRO-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
94
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 126 publications
(103 citation statements)
references
References 32 publications
8
94
0
Order By: Relevance
“…24,55 Similar to our earlier results in human tissue, findings from the current study suggest that CXCL1/CXCR2-mediated signals might influence oligodendrocyte behavior during the course of inflammation in the CNS. Double-Tg, CXCL1, or GFAP single-Tg and wild-type littermate mice all developed EAE when sensitized with MOG peptide, indicating that the two transgenes did not affect disease susceptibility.…”
Section: Discussionsupporting
confidence: 89%
“…24,55 Similar to our earlier results in human tissue, findings from the current study suggest that CXCL1/CXCR2-mediated signals might influence oligodendrocyte behavior during the course of inflammation in the CNS. Double-Tg, CXCL1, or GFAP single-Tg and wild-type littermate mice all developed EAE when sensitized with MOG peptide, indicating that the two transgenes did not affect disease susceptibility.…”
Section: Discussionsupporting
confidence: 89%
“…Increased expression of these factors has also been demonstrated in experimental models of remyelination (Hinks and Franklin, 1999). Cytokines (TGF␤1, TNF␣), chemokines (CXCL1), extracellular matrix components (high-molecular-weight glycosaminoglycans), and developmental cues (Jagged1) have also been shown to regulate the behavior of fetal or perinatal OPCs (McKinnon et al, 1993;Wu et al, 2000;Arnett et al, 2001;John et al, 2002;Back et al, 2005), and to be expressed in MS lesions (Cannella and Raine, 1995;John et al, 2002;Back et al, 2005;Omari et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…The interaction between epithelial cancer cells and stromal cells may be especially important in the development of various epithelial cancers, including breast cancer, colon cancer, prostate cancer, and glioma (34)(35)(36)(37), and in aging (3,(38)(39)(40). Some studies have shown that the interaction of ovarian cancer epithelial cells and stromal cells stimulates the progression of ovarian epithelial cancers (41,42).…”
Section: Discussionmentioning
confidence: 99%